Hydrothermal synthesis, and tailoring the growth of Ti-supported TiO2 nanotubes with thick tube walls. (5th May 2016) - Chu, Mengsha; Tang, Yulin; Rong, Nannan; Cui, Xun; Liu, Feila; Li, Yanhong; Zhang, Chao; Xiao, Peng; Zhang, Yunhuai
Abstract: This work intends to clarify the different effects of sodium salts and organic solvents on the morphology of Ti-supported TiO2 nanomaterials. Titanates were chosen as the precursor to synthesis TiO2 nanomaterials and the morphology controlled synthesis of titanates plays an important role in optimizing the morphology and properties of TiO2 nanostructures. Based on our experiments, titanate nanotubes with thick tube walls (8–10 nm on one side) were obtained in alkaline aqueous solution. The addition of NaCl can lead to the formation of titanate nanosheets, while the addition of NaF or NaBr has no obvious effect on the formation of nanosheets and nanotubes were still obtained. Organic solvents can dramatically influence the morphology and mass loading of titanate on Ti foils. Ethylene glycol can lead to the nanotubes aggregating together to form network structures, while ethanol helps to produce nanosheets. The corresponding possible growth mechanism was preliminarily proposed. The photoelectrochemical performances of titanate-derived TiO2 were investigated, and found that TiO2 nanosheets prepared with NaCl have the best photoelectrochemical performance compared with others. This work provides basis for further study on controlling the morphology and properties of titanate as well as TiO2 nanomaterials on Ti foils. Graphical abstract: Highlights: Ti-supported TiO2 with thick-walled tubes were obtained from titanate precursor. A possible growth mechanism of titanate on Ti foils was proposed. Effects of salts and solvents on the morphology of titanate were analyzed. TiO2 prepared with NaCl has the best photoelectrochemical performance than others.